METHODS OF FORMING UNIVERSITY COMMUNICATION CHANNELS IN DISTANCE WORK CONDITIONS - Grynevych, L. V.; Mirzoiev, D. (The actual problems of regional economy development, 2024)
In the conditions of fierce competition in the market of educational services both in Ukraine and abroad, the issue of attracting applicants to study in institutions of higher education is gaining special relevance. At present, there are many negative external factors that do not contribute to positive dynamics regarding recruitment. Therefore, there is a need to define mechanisms and develop a strategy that will allow changes for the better in the situation with the recruitment of applicants. The first step on this path can be the formation of communication channels of the university with applicants. For this, it is necessary to have a clear plan of action on how to do it. The purpose of the article is to justify the method of forming communication channels of the university in the conditions of remote work. It was developed for foreign applicants. The choice of this target audience is determined by the interests of the state related to the promotion of Ukrainian higher education institutions on the World and European educational markets. The statistical method of observation was chosen as the research method, which made it possible to provide a quantitative and qualitative assessment of the needs of foreign applicants. As a tool, a questionnaire was developed and implemented, which made it possible to form a portrait of the consumer of educational services. The survey was conducted anonymously through the Google platform. The use of this platform made it possible to monitor the survey process, i.e. to draw a conclusion at the initial stage regarding the interest of foreign applicants and applicants in receiving education in Ukraine. The methodology consists of 7 stages, the sequential implementation of which made it possible to single out and describe the channels of communication that should be used to communicate with foreign applicants. Thus, the proposed method of forming university communication channels in the conditions of remote work is of practical importance and can be used in the activities of higher education institutions.